The norepinephrine system and its relevance for multi-component behavior - Mückschel, Moritz; Gohil, Krutika; Ziemssen, Tjalf; Beste, Christian (NeuroImage, 2017)
The ability to execute several actions in a specific temporal order to achieve an overarching goal, a process often termed action cascading or multi-component behavior, is essential for everyday life requirements. We are only at the beginning to understand the neurobiological mechanisms important for these cognitive processes. However, it is likely that the locus coeruleus-norepinephrine (LC-NE) system may be of importance. In the current study we examine the relevance of the LC-NE system for action cascading processes using a system neurophysiological approach combining high-density EEG recordings and source localization to analyze event-related potentials (ERPs) with recordings of pupil diameter as a proximate of LC-NE system activity. N=25 healthy participants performed an action cascading stop-change paradigm. Integrating ERPs and pupil diameter using Pearson correlations, the results show that the LC-NE system is important for processes related to multi-component behavior. However, the LC-NE system does not seem to be important during the time period of response selection processes during multi-component behavior (reflected in the P3) as well as during perceptual and attentional selection (P1 and N1 ERPs). Rather, it seems that the neurophysiological processes in the fore period of a possibly upcoming imperative stimulus to initiate multi-component behavior are correlated with the LC-NE system. It seems that the LC-NE system facilitates responses to task-relevant processes and supports task-related decision and response selection processes by preparing cognitive control processes in case these are required during multi-component behavior rather than modulating these processes once they are operating.
Keywords: dospělí; Executive Function; Female; Psychomotor Performance; pozornost; reakční čas; pupila; Adult; mladý dospělý; ženské pohlaví; Executive function; Attention; Cognitive control; lidé; psychomotorický výkon; noradrenalin; Vegetative factors; EEG; Pupil; Source localization; Male; Sensorimotor integration; Young Adult; inhibice (psychologie); evokované potenciály; Evoked Potentials; Reaction Time; mužské pohlaví; exekutivní funkce; Inhibition, Psychological; Locus Coeruleus; elektroencefalografie; locus coeruleus; Norepinephrine; Electroencephalography; Humans